SENI MURAL SEBAGAI UNSUR POLITIK DALAM KEHIDUPAN SOSIAL - Heri Iswandi (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
Mural is any piece of artwork painted or applied directly on a wall, ceiling other large permanent surface. There are some messages to be conveyed by the makers of mural. It’s to create the condition around him to express of aesthetic, social, and cultural. By this process, it will begin of aesthetic politic and others. The aesthetic is process of effort and making of art to the real thing. There are efforts in the aesthetic of politic to provide a political action by a way of expressing through art media that called mural.Keyword : Mural, social message, political elements.